Thrombotic Thrombocytopenic Purpura, Case Report and Literature Review - Sonda-May, Valeria G.; Dzul-Caballero, Jose E.; Acevedo-Ancona, Lizbeth G.; Carrillo-Vásquez, Carolina; López-Segura, Vanesa (British Journal of Healthcare and Medical Research, 2024)
Background: Thrombotic thrombocytopenic purpura is a rare entity that represents a diagnostic challenge due to clinical manifestations that may be nonspecific. In addition, the diagnostic approach requires expensive and poorly accessible laboratory tests (for example, measurement of ADAMTS13 enzyme activity levels). The first reported case was in 1924, described by Eli Moschcowitz in a 16-year-old girl who died suddenly and in whom the post-mortem biopsy showed thrombi in the kidney, heart and spleen. It is estimated that TTP has an annual incidence of 1.5 to 6 cases per 106 inhabitants, with a prevalence of 10 to 15 cases per 106 inhabitants, and is more frequent in the female sex with a female/male ratio of 2:1. Thrombotic thrombocytopenic purpura (TTP) is characterized by the concomitant appearance of often severe thrombocytopenia, microangiopathic hemolytic anemia, and multiple organ involvement due to ischemia secondary to the formation of thrombi in various parts of the vascular system. The organs most frequently affected are the brain, heart, and kidneys. Currently, it has been identified that the pathophysiology is related to the alteration in the enzyme metalloproteinase with thrombospondin motifs 13 (ADAMTS13), which has protease activity that is responsible for cleaving the ultra-long multimeric chains of the von Willebrand factor (vWF). These alterations can be congenital (recessive mutations of the ADAMTS13 gene) or acquired (formation of antibodies against ADAMTS13). In this review we present the clinical case of a woman from Merida, Yucatan, Mexico, who was admitted to the internal medicine service due to the presence of tension-type headache and jaundice of more than 1 month of evolution. During her care in the emergency room, laboratory studies documented data of intravascular hemolytic anemia and thrombocytopenia, with no involvement of other organs. An approach to autoimmune hemolytic anemia was started, later she presented clinical worsening, neurological involvement (psychosis), increased hemolysis and thrombocytopenia, empirical treatment with steroids was started without response, she was later evaluated by hematology who, due to the clinical characteristics she presented plus the finding of schistocytes in the peripheral blood smear, an approach for PTT was started requesting ADAMTS13 activity levels, and empirical management with plasmapheresis was started, presenting a favorable response. Days later, the results of the studies were collected, reporting 0% ADAMTS13 activity, confirming the diagnosis of PTT. Methods: A search was performed for literature related to the epidemiology, pathophysiology, clinical manifestations, diagnosis, differential diagnosis and treatment of thrombotic thrombocytopenic purpura, as well as literature related to thrombosis, hemolysis, hemolytic anemia, thrombocytopenia, thrombotic microangiopathy, von Willebrand factor in open access search engines and databases such as PubMed, Springer Link, Science Direct, Web of Science and others. Results: We found and analyzed 80 articles that met the search criteria, of which we selected 34 articles with the most relevant information, and with a publication period of less than 10 years. Conclusions: Thrombotic thrombocytopenic purpura is a rare but potentially fatal disease. Its true incidence is unknown, since the clinical presentation is varied with many pathologies that share the same characteristics. In addition, laboratory tests to confirm the diagnosis are not routinely available. A timely diagnosis can improve the prognosis and survival of patients. Currently, there are more therapeutic alternatives available, reducing mortality, which in the past was over 90%, with plasma exchange being the intervention with the greatest benefit.